2018
DOI: 10.1139/cjes-2017-0016
|View full text |Cite
|
Sign up to set email alerts
|

Borehole geophysical log signatures and stratigraphic assessment in a glacial basin, southern Ontario

Abstract: Over the past two decades, the Geological Survey of Canada has used a standardized suite of slim-hole geophysical tools to log 57 polyvinyl chloride cased boreholes drilled in the glacial sediments of southern Ontario. This article documents downhole tool responses (natural gamma, apparent conductivity, magnetic susceptibility, and seismic velocity) in the context of mineralogical characteristics of the region and grain-size data from 28 of the 57 boreholes. Characteristic geophysical properties and (or) patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 46 publications
(75 reference statements)
0
12
0
Order By: Relevance
“…Continuously cored boreholes at Green Lane, Mount Albert, McCowan Rd, Ballantrae, Vandorf Side Rd., King City, Nobleton, Kleinburg, and Vaughan with a cumulative length of 1500 m (Tables 1 and 2) provide important detailed sedimentology to support the key YSA data. Detailed methods for geophysical and borehole logging techniques are presented in Pugin et al (2011), Crow et al (2018), and Knight et al (2008).…”
Section: Geologic and Geophysics Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Continuously cored boreholes at Green Lane, Mount Albert, McCowan Rd, Ballantrae, Vandorf Side Rd., King City, Nobleton, Kleinburg, and Vaughan with a cumulative length of 1500 m (Tables 1 and 2) provide important detailed sedimentology to support the key YSA data. Detailed methods for geophysical and borehole logging techniques are presented in Pugin et al (2011), Crow et al (2018), and Knight et al (2008).…”
Section: Geologic and Geophysics Datamentioning
confidence: 99%
“…stratigraphic framework (e.g., Sharpe et al 2004;Sharpe et al 2018), and with the stratigraphic nomenclature from the Scarborough Bluffs (e.g., Karrow 1967Karrow , 1974Eyles and Eyles 1983). Core samples provide physical property information that is linked to downhole geophysical interpretation (e.g., Pullan et al 2002;Crow et al 2018). The architecture and character of YSA strata are defined from two key sites, Aurora and Queensville, where seismic profiles and continuously cored borehole datasets support construction of a refined geological understanding.…”
Section: Geology and Hydrogeologymentioning
confidence: 99%
“…Eyles et al (2011) proposed the formation of Trafalgar and Waterdown end moraines from a Lake Ontario ice stream. Eyles (2012) also inferred ice stream activity across Manitoulin Island yet no diagnostic features were identified and tested against alternatives, such as spectacular meltwater erosion forms observed on scultped bedrock upflow at French River and downflow on the Bruce Peninsula (e.g., Kor et al 1991;Kor and Cowell 1998;Cowan and Sharpe 2007;Hallet 2011). Eyles and Doughty (2016) concluded that a Lake Ontario ice stream eroded carbonate terrain in eastern Ontario to produce glaciofluvial deposits of the ORM, without integrating detailed local mapping and sediment descriptions that support a glaciofluvial-glaciolacustine character of ORM (e.g., Barnett et al 1998;Russell and Arnott 2003;Russell et al 2004).…”
Section: Ice Streams In Southern Ontariomentioning
confidence: 99%
“…Stratified moraines (e.g., Oak Ridges, Oro, Orangeville, Waterloo, and Dorchester) have a cumulative areal extent of ϳ2500 km 2 and have received the greatest geological attention, as they have been exploited extensively for groundwater and aggregate resources (e.g., Sharpe et al 2002;Bajc et al 2014;Burt and Dodge 2011). In this issue, papers are presented on the Paris-Galt MacCormack et al 2018) and Orangeville moraines (Burt 2018) along with geophysical data from three stratified moraines (Crow et al 2018).…”
Section: Morainesmentioning
confidence: 99%
“…Using a downhole geophysical dataset from continuous-cored boreholes in the Oak Ridges, Oro, and Waterloo stratified moraines, Crow et al (2018) examine the relationship between sediment properties (geochemistry, mineralogy, and grain size) and downhole geophysical signal. They highlight the need for multiple geophysical tools to characterize sedimentary units within a carbonate-dominated glacial basin.…”
Section: Morainesmentioning
confidence: 99%